A Comparison of Sentinel Lymph Node Biopsy to Lymphadenectomy for Endometrial Cancer Staging (FIRES Trial): A Multicentre, Prospective, Cohort Study. Issue 8 (August 2017) - Rossi, Emma C.; Kowalski, Lynn D.; Scalici, Jennifer; Cantrell, Leigh; Schuler, Kevin; Hanna, Rabbie K.; Method, Michael; Ade, Melissa; Ivanova, Anastasia; Boggess, John F.
Abstract : (Abstracted from Lancet Oncol 2017;18:384–392) In more than 75% of women with endometrial cancer, the disease is confined to the uterus. Recurrence risk is defined by surgical staging with lymphadenectomy and helps in the decision to give adjuvant treatment to high-risk patients.